Captive Breeding, Fecundity, and Early Larval Development of Snow Trout (Schizothorax richardsonii) in a Flow-Through Hatchery System - Joshi, Rini; Sharma, Prakash; Gehlot, Bhawna; Arya, Mukul; Pandey, Harsh; Bhatt, Jagesh; Pathak, Bipin Chandra; Sarma, Debajit (Fishery Technology, 2026)
The snow trout (Schizothorax richardsonii), an ecologically and economically important coldwater fish species endemic to the Himalayan and sub-Himalayan regions, is facing declining populations due to overfishing and environmental stressors. This study aimed to establish preliminary data on broodstock development, reproductive performance, and larval rearing of S. richardsonii under captive conditions using a flow-through hatchery system at ICAR-CICFR, Bhimtal. Broodstock were collected at monthly intervals to assess gonadal maturation and spawning behaviour, confirming peak breeding seasons during March–April and September–October. Successful artificial breeding was achieved through hormonal induction using Ovatide at a dose of 0.5 mL/kg body weight for females and 0.3 mL/kg for males, yielding a fertilization rate of 95% and a peak hatching rate of 90% in September. The absolute fecundity ranged from 2000 to 3000 eggs per female, with egg diameter ranging from 2.2 to 2.5 mm. Larval growth exhibited distinct developmental phases, with total length increasing from 8.1 ± 0.15 mm at hatching to 18.3 ± 1.22 mm at 40 days post-hatching. The mean daily growth rate was 0.4 mm/day in early stages, followed by a shift to proportional increase in length and weight after yolk absorption. The cumulative larval survival was 65–70% at 40 days post-hatching under controlled conditions, with water temperature maintained at 20–22 °C, pH 7.2–7.5, and dissolved oxygen ranging between 7.0–8.0 mg/L. Seasonal variations in reproductive indices aligned with previous reports, identifying March and September as the peak spawning periods. This study underscores the potential of induced spawning and highlights the importance of captive breeding and optimized larval rearing techniques for the sustainable propagation of this vulnerable species.